2005
DOI: 10.1038/ng1660
|View full text |Cite
|
Sign up to set email alerts
|

Negative epistasis between the malaria-protective effects of α+-thalassemia and the sickle cell trait

Abstract: The hemoglobinopathies, disorders of hemoglobin structure and production, protect against death from malaria 1 . In sub-Saharan Africa, two such conditions occur at particularly high frequencies: presence of the structural variant hemoglobin S and α + -thalassemia, a condition characterized by reduced production of the normal α-globin component of hemoglobin. Individually, each is protective against severe Plasmodium falciparum malaria 2-4 , but little is known about their malaria-protective effects when inher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
212
3
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(231 citation statements)
references
References 29 publications
(50 reference statements)
14
212
3
2
Order By: Relevance
“…They suggested that this negative epistasis could be the reason why α + thalassemia has not been fixed in any population in sub-Saharan Africa. This situation has been examined theoretically by Williams et al (2005b) and Penman et al (2009) using an epidemiological approach and Hedrick (2011a), using a traditional population genetics approach, found generally similar results. In other words, the single-locus analysis used here may have to be expanded to multiple loci to understand the overall impact on genes conferring resistance to malaria.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…They suggested that this negative epistasis could be the reason why α + thalassemia has not been fixed in any population in sub-Saharan Africa. This situation has been examined theoretically by Williams et al (2005b) and Penman et al (2009) using an epidemiological approach and Hedrick (2011a), using a traditional population genetics approach, found generally similar results. In other words, the single-locus analysis used here may have to be expanded to multiple loci to understand the overall impact on genes conferring resistance to malaria.…”
Section: Discussionsupporting
confidence: 49%
“…Williams et al (2005b) examined these disorders in Kenya in a population that was segregating for both variants (the same one in which we estimated relative fitnesses). In this population, they found that the protection from malaria given by each variant was lost when the two disorders were inherited together in the same individual (see also May et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that the observed patterns of a-and b-globin polymorphism reflect selection for resistance to blood-borne pathogens, as allelic variation in haemoglobin function is known to play an important role in modulating the reduction-oxidation status of red blood cells. In humans, despite the long term knowledge of the selective agent for the most common haemoglobinopathies in sub-Saharan Africa, the existence of negative epistasis between both conditions was reported only recently (Williams et al, 2005). It may therefore prove difficult to unravel the causes of the observed patterns of allele frequency variation at both globin loci in the European rabbit.…”
Section: Functional Significance Of Haemoglobin Polymorphismmentioning
confidence: 90%
“…If the observed patterns of variation at the HBA and HBB genes are attributable to hitchhiking associated with selection at linked loci, in each case the true target of selection is likely to be another closely linked globin gene. In mammals and other vertebrates, haemoglobin polymorphism plays a well-documented role in adaptation to hypoxic environments (Poyart et al, 1992;Weber and Fago, 2004;Storz, 2007;Storz et al, 2007), and in humans, amino acid and deletion polymorphisms in the a-and b-globin genes have been implicated in resistance to malaria (for example, Agarwal et al, 2000;Ohashi et al, 2004;Kwiatkowski, 2005;Williams et al, 2005). In the case of the European rabbit, patterns of HBA and HBB variation across the Iberian Peninsula do not correlate with altitude or any obvious environmental factors.…”
Section: Functional Significance Of Haemoglobin Polymorphismmentioning
confidence: 99%
“…The remarkable variation in the gene frequency between different ethnic groups and regions of Vietnam presumably reflects the complex effects of ancient migrations, variable exposure to selection by malaria and epistatic interactions between the different haemoglobin disorders themselves (Williams et al, 2005;Penman et al, 2009). For example, the lower frequency of b thalassaemia in regions where HbE is particularly common, and vice versa, could reflect different migration patterns but could also result from the variability in the selective effect of two different alleles.…”
Section: Discussionmentioning
confidence: 99%